Alcohol-Induced Liver Injury Is Modulated by Nlrp3 and Nlrc4 Inflammasomes in Mice - DeSantis, David A.; Ko, Chih-wei; Liu, Yang; Liu, Xiuli; Hise, Amy G.; Nunez, Gabriel; Croniger, Colleen M. (Mediators of Inflammation, 2013)
Alcoholic liver disease (ALD) is characterized by increased hepatic lipid accumulation (steatosis) and inflammation with increased expression of proinflammatory cytokines. Two of these cytokines, interleukin-1β (IL-1β) and IL-18, require activation of caspase-1 via members of the NOD-like receptor (NLR) family. These NLRs form an inflammasome that is activated by pathogens and signals released through local tissue injury or death. NLR family pyrin domain containing 3 (Nlrp3) and NLR family CARD domain containing protein 4 (Nlrc4) have been studied minimally for their role in the development of ALD. Using mice with gene targeted deletions for Nlrp3 (Nlrp3−/−) and Nlrc4 (Nlrc4−/−), we analyzed the response to chronic alcohol consumption. We found that Nlrp3−/− mice have more severe liver injury with higher plasma alanine aminotransferase (ALT) levels, increased activation of IL-18, and reduced activation of IL-1B. In contrast, the Nlrc4−/− mice had similar alcohol-induced liver injury compared to C57BL/6J (B6) mice but had greatly reduced activation of IL-1β. This suggests that Nlrp3 and Nlrc4 inflammasomes activate IL-1β and IL-18 via caspase-1 in a differential manner. We conclude that the Nlrp3 inflammasome is protective during alcohol-induced liver injury.